Acquisition of EMG signals during slalom with different ski boots - Petrone, N.; Marcolin, G.; De Gobbi, M.; Nicoli, M.; Zampieri, C. (Science and Skiing IV, 2009)
INTRODUCTION: Aim of the work was the acquisition and analysis of EMG Signals on the legs and the back of an elite athlete during Slalom courses in a snow field. The purpose of the investigation was to develop a reliable method for the acquisition of EMG Signals in the slopes that could be synchronously correlated to the pole passing instants, the skier body posture, the ski angle of attack and the loading actions on the ski. These data are necessary for the biomechanical evaluation of the skiing technique (Zeglinksy et al,1998), the correlation with the ski loading patterns and the functional evaluation of optimised skiing equipments (Muller & Schwameder,2003).